2007
DOI: 10.1002/adsc.200600433
|View full text |Cite
|
Sign up to set email alerts
|

Precision Ethylene/Vinyl Bromide Polymers

Abstract: Here we report the synthesis of precision ethylene/vinyl bromide (EV/B) polymers via metathesis chemistry followed by exhaustive hydrogenation. The polymer primary structures are supported by 1 H NMR, 13C NMR, elemental analysis, TGA, and IR. Thermal analysis by DSC shows that a linear trend exists between increasing bromine content and decreasing melting temperature as bromine is incorporated (as a defect) in the crystalline lattice. In reference to the defect-free chain, a change in phase structure causes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 23 publications
(36 reference statements)
1
43
0
Order By: Relevance
“…The onset T d values of all these copolymer samples are comparable with that of high density polyethylene (HDPE), and these data are also similar to the T d values of previously reported precision polyethylene containing one single ethyl acrylate in the middle of the repeating unit . On the other hand, all of these periodic and random copolymers also exhibited higher thermal stability than precision polyethylene containing vinyl acetate, vinyl halide, and vinyl alcohol units …”
Section: Resultssupporting
confidence: 86%
“…The onset T d values of all these copolymer samples are comparable with that of high density polyethylene (HDPE), and these data are also similar to the T d values of previously reported precision polyethylene containing one single ethyl acrylate in the middle of the repeating unit . On the other hand, all of these periodic and random copolymers also exhibited higher thermal stability than precision polyethylene containing vinyl acetate, vinyl halide, and vinyl alcohol units …”
Section: Resultssupporting
confidence: 86%
“…Acyclic diene metathesis (ADMET) has been utilized extensively for the modeling of polymeric systems, [1][2][3] where linear, defect-free polymers produced by this method serve as pristine models of commercial materials or as novel materials for advanced applications. [4][5][6][7][8][9] Research in this area has shown that imparting these materials with such structural regularity results in a behavior unique to this class of polymers. [1,4,5,7,10] A recent area of effort in our laboratory has been the synthesis of polyethylene (PE) with precise placement of hydrophilic branches.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Figure clearly showed that P0 displayed typical two‐stage decomposition. The first stage occurred within the temperature range from 150 °C to 300 °C, plausibly corresponding to the thermo‐induced release of bromine . Although the as‐prepared polymer P0 was densely‐functionalized with α ‐bromo ester moieties, the absence of β ‐H renders the thermal‐induced release of other bromine‐containing species such as hydrogen bromide unlikely to occur.…”
Section: Resultsmentioning
confidence: 99%